The impact of transactional sex with teachers on public school students in Monrovia, Liberia – a brief report. Issue 4 (2nd October 2017) - Parnarouskis, Lindsey; Stevenson, Anne; Lange, Brittany C.L.; Pullen, Samuel J.; Petruzzi, Liana J.; Dominguez, Silvia; Quiterio, Nicole; Harris, Benjamin; Lekpeh, G. Gondah; Manobah, Burgess; Henderson, David C.; Borba, Christina P.C.
ABSTRACT: Access to education has been shown to strongly influence adolescent health across the world, and strong relationships with teachers has been found to lead to better academic and psychosocial outcomes for students. In many low-income countries where adolescents have less access to education and are more likely to experience poor health outcomes, risky sexual behaviors can exacerbate these challenges by increasing the risk of unintended pregnancy and sexually transmitted infections. This study sought to examine risky behaviors, such as substance use and risky sexual practices, of in-school youth in Liberia, a country in West Africa. Nine focus groups were conducted with public school students in Monrovia, Liberia in April 2012 using a semi-structured guide. The sessions took place in three public schools with n = 72 participants aged 12–20 years old. Following thematic content analysis, a pattern emerged of transactional sex between female students and male teachers, which often led to contrived and coercive relationships for the students. Conversely, participants reported that educators were not disciplined for having sex with students. Interventions to reduce the prevalence of transactional sex within the academic environment would likely protect the well being of school-going youth, particularly female youth, and support students' academic pursuits in Liberia.